The war next-door—A pilot study on Romanian adolescents’ psychological reactions to potentially traumatic experiences generated by the Russian invasion of Ukraine - Maftei, Alexandra; Dănilă, Oana; Măirean, Cornelia (Frontiers in Psychology, 2022)
Romania shares the longest UE border with Ukraine, and since the Russian invasion of Ukraine began, many have been involved in helping the refugees. Consequently, children and adolescents might be directly and indirectly exposed to war-related trauma. In the present exploratory research, we investigated Romanian adolescents' potential risk and protective factors related to the psychological outcomes of war exposure. Our study was conducted shortly after February 24th (i.e., the first invasion day). Participants completed self-reported measures of peritraumatic dissociative experiences, knowledge about the conflict in Ukraine, personal, school, and family implications in volunteering/ helping behavior, discussions about the conflict, threat perception (self and perceived parental threat), anxiety, social media engagement, resilience, and moral elevation. The main findings suggested that participants involved in helping behaviors toward Ukrainian refugees present higher peritraumatic dissociative experiences, anxiety symptoms, and higher moral elevation than boys and participants not involved in these behaviors. Moreover, anxiety symptoms were positively associated with threat perception, peritraumatic dissociation, and social media engagement and negatively related to resilience. Finally, we discuss the implications of our findings concerning their practical utility in managing peritraumatic exposure to war.